Studi Kasus Korupsi di Sektor Pendidikan: Praktik, Pola, dan Dampaknya terhadap Layanan Publik - Ni Nyoman Hariasih Adhi Savitri; Komang Febriyanti Dantes; Ni Komang Irma Adi Sukmaningsih; I Gusti Ayu Apsari Hadi; I Gusti Ngurah Budiyasa (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
Corruption in the education sector poses a serious threat to the integrity of public services and the achievement of national development goals. This study aims to analyze the practices and patterns of corruption in the management of School Operational Assistance (Bantuan Operasional Sekolah/BOS) funds and illegal levies in primary and secondary education settings, while also examining their impact on the quality of public education services. This study employs a descriptive qualitative approach, with data collected through a literature review of various regulations, reports from anti-corruption agencies, and relevant scholarly literature. The findings indicate that weak oversight systems, limited transparency and accountability, and regulatory loopholes are the main factors driving corruption in the management of BOS funds and the practice of illegal levies. These practices directly contribute to unequal access to education, declining education service quality, and weakening public trust in educational institutions. Therefore, strengthening accountability mechanisms, improving transparency in budget management, involving communities in monitoring education funds, and harmonizing regulations are necessary to close legal loopholes that enable irregularities and strengthen the integrity of education governance.